1979
DOI: 10.1097/00006842-197911000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Weight During Treatment for Depression

Abstract: Changes in appetite and weight were examined in a group of 47 carefully diagnosed primary depressives who were treated in a random design with either placebo (N = 17) oramitriptyline [N = 30) over a 35-day protocol. While the amitriptyline treated group as a whole showed a greater gain in weight than did the placebo group (4.5 vs. 0.5 lb, p < 0.05), no differential effects could be demonstrated between drug responders and nonresponders. Likewise, while a consistent relationship between the self-report of decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
3

Year Published

1987
1987
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 10 publications
(10 reference statements)
0
9
0
3
Order By: Relevance
“…In contrast, zimelidine, (which is no longer prescribed but belongs in the category of selective serotonin reuptake inhibitors) did not promote weight gain. Importantly, in our own studies, no relationship between clinical response and weight gain was observed (4,5,10). In fact, weight change during drug treatment was not negatively correlated with that occurring at disease onset; that is, weight gain was not simply areflection of weight lost during the depressive episode.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…In contrast, zimelidine, (which is no longer prescribed but belongs in the category of selective serotonin reuptake inhibitors) did not promote weight gain. Importantly, in our own studies, no relationship between clinical response and weight gain was observed (4,5,10). In fact, weight change during drug treatment was not negatively correlated with that occurring at disease onset; that is, weight gain was not simply areflection of weight lost during the depressive episode.…”
mentioning
confidence: 57%
“…Over the past 15 years, severalnewer medications of a different drug class, the selective serotonin reuptake inhibitors (SSRk), have become available. These drugs are effective as antidepressants, without the side effect of weight The use of two frequently prescribed tricyclic drugs, amitriptyline (4,8,10,14) and imipramine (1,4,5) havemost often been associated with increasing body weight during treatment (Table 1). Moreover, withinthe tricyclic drug class, amitriptyline appears to promote weight gain to a much greater degreethanthe others (Table 1).…”
Section: Abstract: Antidepressants Ingestive Behavior Obesity Depmentioning
confidence: 99%
See 1 more Smart Citation
“…Em um ensaio clínico randomizado controlado, Kupfer et al 19 examinaram mudanças no peso em 47 pacientes depressivos que foram tratados com placebo (n=17) ou amitriptilina (n=30) por um período de 35 dias, com a dosagem de amitriptilina sendo aumentada ao longo do estudo em 50 a 200mg. O grupo com a amitriptilina mostrou um maior ganho de peso do que o grupo placebo (2kg versus -vs 0,2kg, p<0,05), sendo que não houve diferença entre os que responderam ao tratamento e os que não.…”
Section: Antidepressivos Tricíclicos (Adt)unclassified
“…Portanto, esses estudos demonstram haver ganho de peso durante o tratamento agudo da depressão com ADT 19,20 . No período de manutenção, observa-se também aumento no peso corporal, porém sem diferenças em relação ao grupo controle em alguns estudos 28,29 .…”
Section: Antidepressivos Tricíclicos (Adt)unclassified